(untitled) (Legal journal - Research in Legal and Social Sciences, 2023)
This research describes the legal framework of the sovereign countries of the Americas regarding Cannabis sativa. This is a plant known for its medicinal properties and the prohibitions related to its production, sale and consumption. Indeed, as a result of publicity efforts and criminalization by governments, the plant and its derivatives have acquired a negative image in societies. However, thanks to scientific research and its potential in the control of specific ailments such as fibromyalgia and epilepsy, its image has been changing in recent years. This scenario also led to a change in legislation worldwide. Thus, this research adopts a qualitative approach with a non-experimental design. Regarding the type it is documentary with an exploratory-descriptive scope. After analyzing the legislation of American countries regarding regulation, the results show that Cannabis sativa has different legal statuses. In some countries, it is considered illegal; in others, research and medicinal use are allowed; while in some countries, recreational use has even been decriminalized.